2021
DOI: 10.1155/2021/6691734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Metabolic Markers of Hypertension in Chinese Children

Abstract: Background. Studies in adults have shown that several metabolites across multiple pathways are strongly associated with hypertension. However, as yet, to our knowledge, no study has investigated such association in childhood. We, therefore, compared the serum metabolite profile of children with normal and elevated blood pressure (BP) to identify potential metabolic markers and pathways that could be useful for the assessment of pediatric hypertension. Methods. The study included 26 hypertensive children (age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Mann-Whitney U tests, Student's t-tests, and Spearman correlation analyses were performed using SPSS 22.0. Metabolites shown by univariate analysis to have P < 0.05 and VIP > 1 on multivariate analysis were considered reliable differential metabolites [20]. For Spearman correlation analysis, P < 0.05 was considered signi cant [21].…”
Section: Discussionmentioning
confidence: 99%
“…Mann-Whitney U tests, Student's t-tests, and Spearman correlation analyses were performed using SPSS 22.0. Metabolites shown by univariate analysis to have P < 0.05 and VIP > 1 on multivariate analysis were considered reliable differential metabolites [20]. For Spearman correlation analysis, P < 0.05 was considered signi cant [21].…”
Section: Discussionmentioning
confidence: 99%
“…27 To our knowledge, only 2 small studies-both casecontrol in nature-have examined blood metabolite biomarkers with BP or hypertension in children. In 52 Chinese children (ages 6-11 years), Sun et al 28 identified 8 serum metabolites-mainly involved in amino acid and glycerophospholipid metabolism-associated with hypertension. In 456 Canadian children (age 5 years), Azab et al 29 found 13 metabolites associated with the risk of metabolic syndrome, of which BP is a component.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another metabolomics study showed that systolic blood pressure (SBP) and pulse pressure are inversely correlated with glutamine in black adults (14). Similarly, our previous work identified that in children aged 6−11 years with elevated BP, the abundance of glutamine was lower than those with normal BP using a case-control design (15). L-citrulline, the metabolite of glutamine, can increase the synthesis of NO and inhibit arterial tension, which may be the way to regulate BP (16).…”
Section: Introductionmentioning
confidence: 87%